Environmental Pollution Liability Insurance of Health Risk and Corporate Environmental Performance: Evidence From China - Wu, Wenqing; Zhang, Pianpian; Zhu, Dongyang; Jiang, Xin; Jakovljevic, Mihajlo (Frontiers in Public Health, 2022)
Environmental pollution liability insurance (EPLI) is a type of insurance purchased by an enterprise to compensate the loss of the victims in the event of an environmental pollution incident. Although EPLI can realize the post-treatment of environmental pollution to a certain extent, there is still less understanding of whether EPLI can improve the environmental performance of enterprises. This study takes A-share listed companies in heavily polluting industries as the research object, determines the treatment group samples according to the Insurance coverage list published by the Ministry of Environmental Protection in 2014 and 2015, and then constructs the empirical test model. In order to ensure that there is no sample selection bias, the PSM method is used to preprocess the samples in this study to ensure the robustness of the conclusions. The empirical tests show that EPLI can significantly improve corporate environmental performance. Further analysis showed that higher public visibility is conducive to the positive environmental effects of EPLI. Compared with state-owned enterprises, non-state-owned enterprises have more significant implementation effects after introducing EPLI. On further examination, the result indicates that environmental pollution liability insurance can improve environmental performance by alleviating corporate financing constraints. The findings of this paper enrich the theory of the economic impact of environmental pollution liability insurance, which has some meaningful theoretical guidance for enterprises and policy makers.